2022
DOI: 10.3390/plants11020206
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation of Seed Tocopherol Composition in Diverse World Soybean Accessions from Maturity Group 0 to VI Grown in China

Abstract: Tocopherols are natural antioxidants that increase the stability of fat-containing foods and are well known for their health benefits. To investigate the variation in seed tocopherol composition of soybeans from different origins, 493 soybean accessions from different countries (China, USA, Japan, and Russia) belonging to 7 maturity groups (MG 0–VI) were grown in 2 locations (Beijing and Hainan Provinces of China) for 2 years (2017 and 2018). The results showed that significant differences (p < 0.001) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…The same pattern was also observed in lutein, where a decreasing trend of lutein towards late MGs was observed, implying that early matured soybeans accumulate more lutein, which might be attributed to climatic conditions and lutein accumulation pattern in short-season soybean genotypes, which are naturally originated and distributed in high-latitude regions. This concurs with the study of Ghosh et al [ 23 ], who reported that early MG soybean accessions, originated and distributed in high-latitude regions, contained high levels of soybean seed nutritional compositions, including tocopherols.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The same pattern was also observed in lutein, where a decreasing trend of lutein towards late MGs was observed, implying that early matured soybeans accumulate more lutein, which might be attributed to climatic conditions and lutein accumulation pattern in short-season soybean genotypes, which are naturally originated and distributed in high-latitude regions. This concurs with the study of Ghosh et al [ 23 ], who reported that early MG soybean accessions, originated and distributed in high-latitude regions, contained high levels of soybean seed nutritional compositions, including tocopherols.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure S3 , individual chlorophylls, zeaxanthin and β-carotene contents did not show significant responses to MGs, indicating that these components are not more sensitive to the day of maturity. Most importantly, alongside the effects of MGs on the biochemical responses of the targeted pigments, cultivation year had a significant contribution to the contents of carotenoids and chlorophylls ( Table S3 ), implying that seasonal changes can influence the carotenoid and chlorophyll concentrations and the profile of soybeans of different MGs, which is supported by similar reports on soybean isoflavone [ 16 ] and tocopherol [ 23 ]. Additionally, the MG by year interaction had significant effect ( p < 0.001) on lutein, total carotenoids and chlorophylls, which is in consonance with the earlier study on soybean seed nutritional characteristics [ 21 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The current results suggest that cultivars are more reliable resources for the accumulation of tocopherols relative to landraces [41]. Moreover, soybean cultivars are largely developed by targeting high oil content for the oilseed industry by soybean breeders, which indirectly increases the tocopherol content in seeds of soybean cultivars since total tocopherol has a significantly positive correlation with oil [41][42][43]. Thus, breeding for enhanced oil content might have influenced the tocopherol content in the cultivars used in this experiment.…”
Section: Bsa-seq Combined With Haplotype Analysis Can Quickly Identif...mentioning
confidence: 73%
“…As expected, the vitamin E contents of most plant-based beverages were higher than those of cow’s milk, with the soy and almond drinks providing the highest contributions to the RDA for this vitamin reaching up to 47% of RDA ( Supplementary Table 7 ). Both almond and soy are naturally high in vitamin E ( 34 , 67 ). The vitamin E concentrations in the rice, oat, and spelt drinks might have benefited from the addition of sunflower oil that is known to be naturally rich in vitamin E ( 34 ).…”
Section: Discussionmentioning
confidence: 99%